ANALISIS RENCANA TATA TANAM GLOBAL (RTTG) TERHADAP KINERJA DAERAH IRIGASI LUASAN LEBIH DARI 3000 HA - Hesti Triana; Antonius Suryono; Esti Widodo (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2016)
The potential of irrigated land in the province of Papua untapped Seara clear, very suitable to serve as land development and land irrigation potential has not been clearly identifed. Koya is one of the transmigration program development that is expected to serve as a granary for the City and District mainstay Jayapura.Debit average67.003 m3 / sec for irrigation service area in Koya planned area of 4970 ha, Dam Tami sufficient to meet the water needs of irrigation areas Koya, which is an area of 3638 ha to 2978 ha of paddy details and the rest of the farm / fishing area of 660 ha. So that the provision of irrigation water will be carried out continuously. The system of planting(PTT) of the analytical results obtained RTTG variation 2 with cropping pattern Paddyrice-paddy rice (early planting in December and June) and Nila-Nila-Nila as RTTG elected, and after the simulation of the water balance and allocation model discharge surplus water obtained a total of 80.724 m3 / sec. But needs to be studied rampant land conversion, both of farmland to the fishery / pond, as well as the existence of human resources locals to expertise in farming